Synthesis, X-ray characterization, DFT calculations and Hirshfeld surface analysis studies of carbohydrazone based on Zn(ii) complexes. Issue 1 (26th November 2015) - Mahmoudi, Ghodrat; Bauzá, Antonio; Rodríguez-Diéguez, Antonio; Garczarek, Piotr; Kaminsky, Werner; Frontera, Antonio
Abstract : Five Zn(ii ) complexes based on a N4 O core carbohydrazone ligand have been synthesized and X-ray characterized. The noncovalent interactions that govern the crystal packing have been rationalized by means of DFT calculations. Abstract : In this manuscript we report the synthesis and X-ray characterization of five complexes of Zn(ii ) based on a N4 O core carbohydrazone ligand (H2 L); i.e. [Zn4 (HL)4 ](CH3 OH)4 (NO3 )4 (1 ), [Zn4 (HL)4 ](ClO4 )4 (2 ) [Zn4 (HL)4 ][Zn(SCN)4 ](NO3 )2 (3 ) [Zn(SCN)4 ](H4 L)(CH3 OH)2 (4 ) and [Zn4 (HL)4 ](NO3 )4 (H2 O) (5 ). Structurally characterized tetranuclear Zn(ii ) complexes, as those reported herein, are scarcely found in the literature. In the crystal structures of several compounds, N–H⋯S hydrogen bonds, anion–π and π–hole interactions are described and analysed by means of density functional theory (DFT) calculations since they play an important role in the construction of three-dimensional supramolecular frameworks. Moreover, the noncovalent interactions have been also analysed using Hirshfeld surface analysis.